LEGAL EXPLANATION ON THE RESPONSIBILITY OF THE HOUSEHOLD INDUSTRY OWNER IN FOOD SAFETY VIEWING FROM CONSUMER PROTECTION LAW IN BUDE NURUL CATERING - Merizqa Ariani; Nur Hadiyati (ConCEPt - Conference on Community Engagement Project, 2022)
Food is the main need to be consumed as a source of physical health so that they can carry out their daily routines as they should. Food can be consumed by humans directly or through processing. Processed food is often sold to the public or made into a business. Business in the food sector is certainly a business that is very much in demand. However, it is not uncommon for some people to use hazardous materials in food in order to gain more profits and to compete with other entrepreneurs. These hazardous materials such as rhodamine B, borax etc. So that consumers are often disadvantaged, especially in terms of health. Efforts made by the government is to issue Law no. 8 of 1999 as a form of legal protection for consumers. For this reason, this counseling is carried out to business actors with the aim of understanding things such as: rights and obligations for business actors, rights and obligations for consumers, prohibited actions for business actors and the responsibilities of business actors as stated in Law no. 8 of 1999. The method used in community service activities is the lecture method and then managed in a qualitative form. The results obtained from the implementation of this counseling are that business actors clearly understand what are the rights and obligations of business actors and know the responsibilities of business actors.